Detection of Vibrio parahaemolyticus from saltwater fish samples by Vp-toxR PCR - Anjay, Dr.; Das, Suresh; Kumar, Ashok; Kaushik, Purushottam; Kurmi, Baleshwari (Indian Journal of Fisheries, 2013)
A total of sixty numbers of saltwater fish samples were collected and analysed by Vp-toxR PCR assay, directly from alkaline peptone water (APW) inoculated with samples and also by colony PCR from characteristic colonies on thiosulfate citrate bile salts sucrose (TCBS) agar. Vp-toxR PCR assay detected 5 (8.3%) samples positive for Vibrio parahaemolyticus directly from APW; whereas colony PCR detected 47 (78.3%) samples positive for the organism. Based on the results of the present study, it may be recommended to use colony PCR as a method suitable for detection of V. parahaemolyticus from saltwater fish samples.